Baseline Findings of an HIV Incidence Cohort Study to Prepare for Future HIV Prevention Clinical Trials in Kisumu, Kenya - Wairimu Chege; Sherri L Pals; Eleanor McLellan-Lemal; Sanjyot Shinde; Monicah Nyambura; Frederick O Otieno; Deborah A Gust; Robert T Chen; Timothy Thomas (Journal of Infection in Developing Countries)
Introduction: In an analysis of baseline findings of an HIV incidence cohort study, an assessment was made of HIV prevalence among persons presenting for enrollment and any differences in demographic characteristics between persons not enrolled compared to those enrolled.  We also described and compared HIV risk behaviors in males and females enrolled in the study. Methodology: A computer-assisted survey was administered to collect baseline demographic and HIV risk data from 1,277 men and women aged 18-34 years. Testing for HIV and other sexually transmitted infections (STI) was conducted.  Out of 1,277 persons prescreened for eligibility, 625 were enrolled. Results: HIV prevalence of all persons who completed screening was 14.8% (females: 21.1%; males: 8.1%).  The odds of being enrolled in the study were higher for persons 18-24 years compared to those 30-34 years of age [adjusted odds ratio (AOR)=2.18, CI=1.13, 4.21] and males compared to females [AOR=2.07, CI=1.43, 2.99].  Among those enrolled in the study, the most prevalent HIV risk behaviors were unprotected sex (49%), alcohol use (45%), and transactional sex (30%) in the last three months. Compared to females, a significantly greater proportion of males reported using any alcohol or recreational drug in the last three months, a history of oral sex, sex with partner other than a spouse or main partner, ever having a blood transfusion, ever being treated for an STI, and having knowledge of their last HIV test result. Conclusion: The Kisumu Field Station successfully recruited individuals with HIV risk characteristics for the HIV incidence cohort study.